Rural transport and traction enterprises for improved livelihoods - Crossley, Peter; Chamen, Tim; Kienzle, Josef; Food and Agriculture Organization of the United Nations (Rome : Rural Infrastructure and Agro-Industries Division, Food and Agriculture Organization of the United Nations, 2009)
This booklet focuses on promoting transport and traction services as viable diversification enterprises for smallholder farmers and other in rural areas. It considers the benefits that can arise from such enterprises, not only for smallholders themselves, but also to local communities in overall terms through increased productivity, improved and faster marketing, better mobility and reduced drudgery.--Publisher's description
Keywords: Rural transportation; Animal traction; Infrastructure (Economics)